STRATEGIES FOR DIVERSIFICATION OF ENTERPRISE ACTIVITIES: CLASSIFICATION, PRINCIPLES OF IMPLEMENTATION AND STAGES OF DEVELOPMENT - MARTIYANOVA, Maryna; KUPRINA, Nataliia; BASIURKINA, Nataliya; MOMOT, Kamila (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article is devoted to developing a classification of strategies for the diversification of enterprise activities, the principles of their implementation, and the key stages of development. It is substantiated that diversification strategies of enterprise activities are essential for ensuring sustainability, competitiveness, and development in a changing market environment. It is determined that by sectoral affiliation, mono-sectoral, multi-sectoral, and multi-sectoral unrelated diversification are distinguished. Attention is also focused on vertical, horizontal, concentric, and conglomerate diversification strategies. The essence, advantages, and disadvantages of each of them are defined. Varieties of vertical and horizontal diversification are considered, such as full integration, expansion of the range of products, and expansion by geographical location. The essence of related and unrelated diversification strategies and the possibility of their combination in cross-cutting and mixed strategies are disclosed. It is substantiated that the presented classification provides an opportunity for business owners and managers of enterprises to note and analyze various diversification strategies. It allows them to focus on those strategies that may be most effective in the context of a particular activity, especially in an environment of unstable functioning. The principles of the diversification strategy are clarified: consistency, flexibility, relevance, synergy, innovation, and distribution of risks. The main stages of developing a diversification strategy are presented, which include: analysis of the strengths and weaknesses of the business; determination of the goal, objectives, and expected results of diversification; search for possible areas of diversification; assessment of promising areas of diversification; analysis of the total investment portfolio; making a decision on the most optimal direction of diversification; monitoring the implementation of the diversification strategy.